Characteristics of Loss to Follow-Up Patient in Drug-Sensitive Pulmonary TB in Medan - Sari Mardia, Rina; Sinaga, Bintang YM; Siagian, Parluhutan; Taufik, Ashar (Journal of Society Medicine, 2024)
Introduction: Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis. Adherence to TB treatment is a complex and dynamic phenomenon with various interacting factors. The characteristics of loss to follow-up patients include social, clinical, and economic characteristics. The Aim of study was to identify characteristics of loss to follow-up patients in drug-sensitive pulmonary TB in Medan. Method: This research is a descriptive study using a cross-sectional approach. All variables were measured and observed at a time during the study. The study was conducted at RSUP Adam Malik Medan and Prof. Dr. Chairuddin P. Lubis USU Hospital in loss to follow-up TB patients diagnosed bacteriologically that meet the criteria of inclusion and exclusion. This study used data from medical records and questionnaires. Independent variables include age, gender, educational level, employment, marital status, family history of lung tuberculosis, attitudes to TB treatment, social support, health services, and reasons for loss to follow-up. Results: Out of 40 patients with loss to follow-up pulmonary tuberculosis, the majority were patients in the age range of 45-65 years (n=26.65%), male (n=31.77,5%), equal level of high school education (n = 24.60%) had a fixed job (n=33.82.5%), marital status (n=33.90%), had no family history of lung tuberculosis (n=36.90%), poor attitude to TB treatment (n=36.90%), received low social support (n=51.52,5%), and received less supported health care services (n<33.82,5%). Reasons patients TB SO quit taking medication presented in this study vary, among others due to the side effects of TB drugs, patients choosing herbal drugs, already feeling healthy, laziness consuming TB medication, being embarrassed with pulmonary TB disease, not taking lung TB drugs because no one carries or has no transportation costs. Conclusion: The majority of patients with drug-sensitive pulmonary tuberculosis who quit their medication in the fields are between 46 and 65 years of age, male sex, high school graduates of equal degree, have a fixed job, marital status, have no family history of TB, have an inferior attitude to TB treatment, receive low social support, and receive less supportive health services. Reasons for loss to follow-up for SO TB patients vary, including TB drug effects, clinical, and economic.